Prediction of the Flash Point of Binary and Ternary Straight-Chain Alkane Mixtures. (23rd April 2014) - Li, X.; Duan, P. P.; Sun, K. N.; Yan, X.
Abstract : The flash point is an important physical property used to estimate the fire hazard of a flammable liquid. To avoid the occurrence of fire or explosion, many models are used to predict the flash point; however, these models are complex, and the calculation process is cumbersome. For pure flammable substances, the research for predicting the flash point is systematic and comprehensive. For multicomponent mixtures, especially a hydrocarbon mixture, the current research is insufficient to predict the flash point. In this study, a model was developed to predict the flash point of straight-chain alkane mixtures using a simple calculation process. The pressure, activity coefficient, and other associated physicochemical parameters are not required for the calculation in the proposed model. A series of flash points of binary and ternary mixtures of straight-chain alkanes were determined. The results of the model present consistent experimental results with an average absolute deviation for the binary mixtures of 0.7% or lower and an average absolute deviation for the ternary mixtures of 1.03% or lower.